Horizontal Transmission of the Heritable Protective Endosymbiont Hamiltonella defensa Depends on Titre and Haplotype - Kaech, Heidi; Vorburger, Christoph (Frontiers in Microbiology, 2021)
Secondary endosymbionts of aphids have an important ecological and evolutionary impact on their host, as they provide resistance to natural enemies but also reduce the host’s lifespan and reproduction. While secondary symbionts of aphids are faithfully transmitted from mother to offspring, they also have some capacity to be transmitted horizontally between aphids. Here we explore whether eleven isolates from three haplotypes of the secondary endosymbiont Hamiltonella defensa differ in their capacity for horizontal transmission. These isolates vary in the protection they provide against parasitoid wasps as well as the costs they inflict on their host, Aphis fabae. We simulated natural horizontal transmission through parasitoid wasps by stabbing aphids with a thin needle and assessed horizontal transmission success of the isolates from one shared donor clone into three different recipient clones. Specifically, we asked whether potentially costly isolates reaching high cell densities in aphid hosts are more readily transmitted through this route. This hypothesis was only partially supported. While transmissibility increased with titre for isolates from two haplotypes, isolates of the H. defensa haplotype 1 were transmitted with greater frequency than isolates of other haplotypes with comparable titres. Thus, it is not sufficient to be merely frequent – endosymbionts might have to evolve specific adaptations to transmit effectively between hosts.